Pemantauan Kadar Obat Antiepilepsi dalam Darah terhadap Clinical Outcome pada Pasien Epilepsi di RSPAD Gatot Soebroto dengan Pendekatan Farmakokinetika - Dini Permata Sari; Winda Septyani Sianipar (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2024)
The use of antiepileptic drugs requires monitoring of blood drug levels because antiepileptics are drugs with a narrow therapeutic index. This study was conducted to determine the relationship between the accuracy of blood antiepileptic drug levels and clinical outcomes in epilepsy patients at RSPAD Gatot Soebroto using a pharmacokinetic approach. This study is an analytical observational study with a retrospective cross-sectional study of epilepsy patients using antiepileptic drugs from January 2023 to January 2024 at RSPAD Gatot Soebroto Jakarta. The results of this study showed that the most antiepileptic drug was valproic acid (38.55%). Of the 32 patients using valproic acid, there were 22 uses of valproic acid below the therapeutic range (<50 mg/L), 10 uses of valproic acid within the therapeutic range (50–100 mg/L). Of the 22 uses of phenytoin, there were 4 uses of phenytoin below the therapeutic range (<10 mg/L), 17 uses of phenytoin within the therapeutic range (10–20 mg/L), and 1 use of phenytoin above the therapeutic range (>20 mg/L). Of the 10 uses of carbamazepine, 1 use of carbamazepine was below the therapeutic range (<4 mg/L), and 9 uses of carbamazepine were within the therapeutic range (4-12 mg/L). Of the 4 uses of levetiracetam, there were 4 uses of levetiracetam below the therapeutic range (12-46 mg/L), and 1 use of oxcarbazepine had a therapeutic range below the therapeutic range (3-35 mg/L). In clinical outcomes within 6 months, 18.07% of patients experienced seizures after receiving antiepileptic drug therapy, and 81.93% of patients experienced seizure-free for up to 6 months. The conclusion of this study is that a p-value of >0.05 is obtained, which means that there is no relationship between clinical outcomes and the accuracy of antiepileptic drug levels in the blood of epilepsy patients. This is because there are other pharmacokinetic parameters that cannot be predicted, so it is necessary to monitor antiepileptic drug levels directly on patients to improve the desired clinical outcomes.